Pathways toward a positive future - Groezinger, Rosa; Verbree, Rosanne; Hicks, Cheryl; Ritola, Maria (Ökologisches Wirtschaften - Fachzeitschrift, 2013)
Examples of emerging sustainable living practices can be found in all parts of the world. However, negative impacts from production and consumption remain and broad shifts toward sustainable lifestyles are not yet occurring. How can future scenarios and road mapping be used to develop actions to support the transition toward sustainable living?